Satisfaction with life and psychological symptoms among international students in Ghana and their correlates - Sam, D.L.; Tetteh, D.K.; Amponsah, B. (International Journal of Intercultural Relations, 2015)
The goal of this study was to understand the adaptation of international students in Ghana focusing on correlates of satisfaction with life and psychological symptoms. The sample for the study was 151 international students, of which 97 originated from West Africa and 54 from Western countries, mostly from North America. Participants responded to a questionnaire with scales accessing satisfaction with life, psychological symptoms as outcomes and a number of psychosocial factors and academic related issues. Results indicated that on the, the students were satisfied with their life and had few psychological symptoms. However, students from West Africa reported poorer satisfaction with life, contrary to our expectations. Satisfaction with life and psychological symptoms were unrelated, and these two outcomes were predicted by different factors. Hierarchical multiple regressions indicated that our predictors could account for 30% of the explained variance in psychological symptoms and 42% in satisfaction with life. In spite of the fact that our participants were students, academic related factors did not contribute significantly to the students’ psychological symptoms, except for academic strain which accounted for about 17% of the explain variance in satisfaction with life. Contrary to our expectation, English language proficiency was related to more psychological symptoms, and this relationship was partially mediated by perceived discrimination. The results are discussed in the light of general acculturation theory on sojourners within the Ghanaian cultural context.
Keywords: International students; Satisfaction with life; Psychological symptoms; Acculturation; Adaptation; Ghana; West Africa; Western countries